Regulatory agencies and regulatory risk - Günter Knieps; Hans-Jörg Weiß (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2007)
The aim of this paper is to show that regulatory risk is due to the discretionary behaviour of regulatory agencies, caused by a too extensive regulatory mandate provided by the legislator. The normative point of reference and a behavioural model of regulatory agencies based on the positive theory of regulation are presented. Regulatory risk with regard to the future behaviour of regulatory agencies is modelled as the consequence of the ex ante uncertainty about the relative influence of interest groups in the regulatory process. The problem of regulatory risk is analysed separately in competitive network areas and in non-competitive network areas. For both cases a specific measure of regulatory risk is proposed. But measurement and compensation are different issues. The im-possibility of compensating for regulatory risk is demonstrated. Finally, the disaggregated regulatory mandate is presented as an institutional reform approach.
Keywords: 330; Regulierung; Risiko; Aufsichtsbehörde; Diskretionäre Politik; Netzzugang